1997
DOI: 10.1136/jech.51.6.705
|View full text |Cite
|
Sign up to set email alerts
|

Distressed or relieved? Psychological side effects of breast cancer screening in The Netherlands.

Abstract: Study objectives-To assess the psychological impact of mammographic screening on women with non-malignant outcomes after attending the Netherlands' National Breast Cancer Screening Programme. Design-During one year all women with false positive test results (95) in a screening area were invited for the study. Each false positive was matched with two women with normal mammograms with respect to age and municipality. A random reference group of 400 was drawn from the female population in an area not yet included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 12 publications
4
49
0
1
Order By: Relevance
“…Aro et al [6] argued that, although some shortterm distress after a positive result could be found, these are moderate, and that general cancer-specific distress is more of a problem. Scaf-Klomp et al [22] argued that a false-positive test does not cause adverse effects longer than 8Á10 weeks and that differences in psychological functioning between false positives and negatives rather was due to a sense of relief among the negatives. Other studies have indicated the presence of long-term effects, following a false positive result [3,4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Aro et al [6] argued that, although some shortterm distress after a positive result could be found, these are moderate, and that general cancer-specific distress is more of a problem. Scaf-Klomp et al [22] argued that a false-positive test does not cause adverse effects longer than 8Á10 weeks and that differences in psychological functioning between false positives and negatives rather was due to a sense of relief among the negatives. Other studies have indicated the presence of long-term effects, following a false positive result [3,4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…3,38 As this was the first unit on the island using direct digital mammography, radiologists were new to the equipment possibly leading to increased recall rates. 39 Such high recall rates may also arise from the local absence of consensus or arbitration of double reading. Other studies have suggested that double reading by consensus or arbitration, although being more labour intensive, decreases the recall rate.…”
Section: Discussionmentioning
confidence: 99%
“…37 One study found that 30% of recalled women felt very anxious on receipt of their recall letter, whilst another study reported that 40% of women reported feeling very frightened when they received their recall letter. 38,39 16% of respondents felt certain that they had breast cancer. 38,39 Such a psychological impact was reported by recalled women before 40 , during 41 , and immediately after recall.…”
Section: Psychological Impact Of Recallmentioning
confidence: 99%
See 1 more Smart Citation
“…En esta misma línea, se ha hallado que no era probable que de manera global el cribado de cáncer de mama genere efectos psicológicos adversos en las mujeres sanas, incluso cuando el resultado era un falso positivo. Atribuyéndose las diferencias en el funcionamiento psicológico entre las mujeres con un resultado falso positivo y las mujeres con un resultado negativo con más probabilidad a sentimientos de alivio en el grupo cuyos resultados fueron negativos que a un aumento de la ansiedad y del malestar psicológico en el grupo al que se le dio un resultado falso positivo (26) . Comparándose mujeres que habían recibido un resultado falso positivo con mujeres que habían recibido resultados claros, tres y doce meses después de haber atendido a las pruebas posteriores se ha encontrado que no había diferencias con respecto a la ansiedad entre ambos grupos (27) .…”
Section: Introductionunclassified